1977
DOI: 10.4039/ent109789-6
|View full text |Cite
|
Sign up to set email alerts
|

DISTRIBUTION OF OVIPOSITIONAL ATTACKS BY PARASITOIDS ON OVERWINTERING LARVAE OF THE SPRUCE BUDWORM, CHORISTONEURA FUMIFERANA (LEPIDOPTERA: TORTRICIDAE)

Abstract: Can. Ent. 109: 789-796 (1977) Parasitism by Apanteles and Glypta spp. on spruce budworm in five localities in Quebec in 1975 was exceptionally high, averaging 52%. The frequency distribution of attacks of these species, and the outcome of inter-and intraspecific progeny competition are described, using dissection data. Superparasitism occurred on a Poisson distribution, but rates of multiparasitism lower than expected indicate interference between Apanteles and Glypta spp. ResumeDan cinq localites au Quebec … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

1983
1983
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…The full-grown parasitoid larva emerges to spin a cocoon when the budworm is in its fourth or fifth instar (Brown 1946). Apantelesfumiferanae may parasitize more than 50% of spruce and jack pine budworm populations (McLeod 1977;unpublished data). The mortality caused by these parasitoids is relevant for forest protection because the host is killed before extensive feeding damage occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The full-grown parasitoid larva emerges to spin a cocoon when the budworm is in its fourth or fifth instar (Brown 1946). Apantelesfumiferanae may parasitize more than 50% of spruce and jack pine budworm populations (McLeod 1977;unpublished data). The mortality caused by these parasitoids is relevant for forest protection because the host is killed before extensive feeding damage occurs.…”
Section: Introductionmentioning
confidence: 99%
“…The reasons for this are not clear. The experimental methods insured a surplus of hosts and, moreover, A. fimiferanae will frequently use the same host for repeated oviposition (McLeod 1977). It is possible that the manner in which hosts were offered, as sedentary larvae in hibernacula, was an unnatural or difficult situation for optimum oviposition.…”
Section: Resultsmentioning
confidence: 99%
“…Apantelesfumiferanae appears to be ubiquitous in populations of these budworms. Miller and Renault (1976) found that A. fumiferanae was one of the few species of parasitoid that was present every year over a 12year period of low spruce budworm density in New Brunswick and the parasitoid is routinely found in high-density budworm populations, sometimes at frequencies exceeding 50% (McLeod 1977). Brown (1946) summarized the earlier observations on A. fumiferanae and provided descriptions of the life stages.…”
Section: Introductionmentioning
confidence: 99%
“…Although G. fumiferanae is well adapted to its host it does not parasitize over 25% of them even at high host population levels (Miller 1960;McLeod 1977). Why does it not parasitize a much higher percentage particularly in abundant host populations?…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, if this is so, functional adaptation to survival on sparse host populations may prevent the species from exploiting a sudden or periodic abundance of hosts. In fact, G. fumiferanae is often proportionately less abundant in high host populations (McLeod 1977).…”
Section: Discussionmentioning
confidence: 99%